1999
DOI: 10.1348/135532599167842
|View full text |Cite
|
Sign up to set email alerts
|

When the killer suffers: Post‐traumatic stress reactions following homicide

Abstract: Objectives. The present study aimed to consider the extent to which post‐traumatic stress disorder (PTSD) occurs after homicide and to examine characteristics of the offence and the offender which contribute to the development of these symptoms. It was proposed that type of violence (reactive versus instrumental) would be related to PTSD symptoms. Using Blackburn's typology of violent offenders, it was also hypothesized that primary and secondary psychopath, controlled and inhibited types would demonstrate dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 18 publications
5
65
0
Order By: Relevance
“…Full emotional realization is often an integral step for resolution in PTSD therapy (see Foa & Hearst-Ikeda, 1996), and therefore must be addressed with such clients. As previously mentioned, an association between PTSD and violence perpetration as been found in other samples (e.g., Jakupcak & Tull, 2005;Pollock, 1999;Stuart, Moore, Gordon, Ramsey, & Kahler, 2006;Taft et al, 2005). Together, these results suggest that further investigation should focus on narcissistic and antisocial batterers in light of the incidence of reported physical violence both within and outside of intimate relationships.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Full emotional realization is often an integral step for resolution in PTSD therapy (see Foa & Hearst-Ikeda, 1996), and therefore must be addressed with such clients. As previously mentioned, an association between PTSD and violence perpetration as been found in other samples (e.g., Jakupcak & Tull, 2005;Pollock, 1999;Stuart, Moore, Gordon, Ramsey, & Kahler, 2006;Taft et al, 2005). Together, these results suggest that further investigation should focus on narcissistic and antisocial batterers in light of the incidence of reported physical violence both within and outside of intimate relationships.…”
Section: Discussionsupporting
confidence: 78%
“…It has also been found that women who are court mandated to attend violence intervention programs, as compared with women in the general population, may experience elevated levels of post-traumatic stress disorder (PTSD) symptoms (Goldenson, Geffner, Foster, & Clipson, 2007;Stuart, Moore, Gordon, Ramsey, & Kahler, 2006). As an association between PTSD symptoms and an increase in the likelihood of engaging in subsequent violent acts has been found in other samples (e.g., Pollock, 1999), this is certainly an important facet of violence perpetration in the domestic context. It is additionally apparent that, as is the case with males, identifying features of female who perpetrate IPV has important applied implications.…”
Section: Introductionmentioning
confidence: 99%
“…These crimes may deeply affect the individuals involved both physically and psychologically, and have been reported to have long-lasting consequences for the stricken human being (see, e.g. Blackburn, 1993;Dahl, 1992;Kilpatrick, Resnick, Saunders & Best, 1998;Pollock, 1999). Moreover, besides the direct involvement in violent or sexual crimes, anyone who engages empathically with trauma victims can be, through a cumulative process, affected by vicarious traumatization through listening to traumatic material while fulfilling a caring role.…”
Section: Traumatic Factors the Crime And The Interviewmentioning
confidence: 99%
“…The impact of the murder for its perpetrator would be greater when the murder is against his beliefs and values. So, if the murder is something that the perpetrator condemns and considers wrong, it will generate more guilt and regret [30]. As we found on our study, the unsystematic planning of the murder will be related to the fragility of decision making process that leads to the murder, which relates with the perception of the murder as inconsonant with the perception of self that, as Pollock [30] states, will lead to more deep regret and guilt, as we found in our participants.…”
Section: Discussionmentioning
confidence: 99%